Interaction of Water with Atomic Layer Deposited Titanium Dioxide on p‐Si Photocathode: Modeling of Photoelectrochemical Interfaces in Ultrahigh Vacuum with Cryo‐Photoelectron Spectroscopy. Issue 11 (3rd May 2021) - Cottre, Thorsten; Fingerle, Mathias; Kranz, Melanie; Mayer, Thomas; Kaiser, Bernhard; Jaegermann, Wolfram
Abstract: This study combines cryo‐photoelectron spectroscopy and electrochemical analysis techniques to investigate the p‐Si/SiO2 /TiO2 /H2 O system in the context of water‐splitting. Atomic layer deposition is used for the preparation of a TiO2 thin film coating for a p‐Si/SiO2 photocathode. First, an interface experiment is performed to study the contact properties of the interface between p‐Si/SiO2 and TiO2 . For the p‐Si/TiO2 heterojunction, a downward band bending of 0.3 eV is found for the p‐Si toward the interface. Second, a water adsorption experiment is conducted, which allows the investigation of the surface chemistry of the TiO2 coating in contact to water. A direct correlation between the amount of surface hydroxide species, formed due to water dissociation, and Ti 3+ defect state density is found. Furthermore, a surface water species can be identified in addition to the commonly found bulk molecular water. Together with the results from a Mott–Schottky analysis, a complete energy level alignment can be constructed. Abstract : Cryo‐photoelectron spectroscopy combined with electrochemical methods is used to study the interaction of water with atomic layer deposited titanium dioxide on p‐Si. A direct correlation between the amount of surface hydroxide species, formed due to water dissociation, and Ti 3+ defect state density is found. Furthermore, another surface water species can be identified besides the commonly found bulk molecular water.